Exploring Consumer Preferences: Attribute Analysis and Satisfaction with Cavendish Bananas - Maulana Sudrajat, Prama Hasta Aditya; Wisnujati, Nugrahini Susantinah; Sastryawanto, Hary (SCIENTIA: Journal of Multi Disciplinary Science, 2024)
The Cavendish banana is known for its quality attributes, including price, taste, skin color, cleanliness, and more. These attributes, when meeting consumer expectations, can lead to high consumer satisfaction. Improving these quality attributes can enhance consumer satisfaction and encourage increased consumption of the fruit. This study aims to analyze the impact of the quality attributes of Cavendish bananas on consumer satisfaction in Sidoarjo. The research was conducted on consumers who purchase directly from small vendors and supermarkets in Sidoarjo using the Accidental Sampling technique. Data were collected through interviews and observations, with a sample size of 12 individuals from street vendors and supermarkets in Sidoarjo. The data analysis method used was qualitative, specifically Qualitative Cross Section data. The results indicate that the majority of Cavendish banana consumers in Sidoarjo responded positively to the attributes of the bananas, including price, taste, quality, and the cleanliness of the display areas.